Pemanfaatan Pupuk Organik Untuk Meningkatkan Produktivitas dan Keberlanjutan Pertanian Di Desa Paku Jaya Kecamatan Morosi Kabupaten Konawe - Gandri, La; Indriyani, Lies; Fahidu, Wa Ode Hastiani; Manan, Abdul; Hasani, Umar Ode; Bana, Sahindomi; Teke, Junartin; Muhsimin, Muhsimin; Agusrinal, Agusrinal; Fitriani, Vivi; Sudia, La Baco; Mutmainnah, Laily (AKSILAR: Akselerasi Luaran Pengabdian Masyarakat, 2025)
Paku Jaya Village is a village where the majority of the population depends on the agricultural sector for their living. The main products are the cultivation of rambutan, dragon fruit, and oranges. The problems faced by partners relate to the application of organic fertilizer, not only providing necessary nutrients for plants, but also improving soil health and reducing the risk of environmental degradation. The aim of the community service program (PKM) is to solve the problems faced by partners by conducting outreach, FGD (Focus group discussion), and training. The expected impact of this program is that partners will have community knowledge regarding environmentally friendly agricultural practices. The methods for implementing the PKM program are socialization, FGD, and training. The expected target of PKM is to be able to provide practical recommendations for farmers and stakeholders in developing agricultural strategies that are more environmentally friendly and economical